KEEFEKTIFAN PEMBELAJARAN STORYTELLING DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS VII SMP MUHAMMADIYAH LIMBUNG: KEEFEKTIFAN PEMBELAJARAN STORYTELLING DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS VII SMP MUHAMMADIYAH LIMBUNG - Khaerani, Nur Rafni; Rosdiana; Fajrul Khaer (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to find out the effectiveness of storytelling learning in improving the writing skills of students in class VII of Muhammadiyah Limbung Junior High School. In fact, students at the Junior High School (SMP) level are already good at writing. However, the reality in the field shows that students' writing skills are still relatively low. Writing skills are one of the important aspects in learning the Indonesian language that is still a challenge for many students, especially in developing ideas in a sequential and interesting way.The method used in this research is a quantitative method with a quasi-experimental design. The research sample consists of two classes, namely the experimental class using the storytelling method and the control class using the conventional method. The instrument used is a narrative writing test before and after treatment. The data was analyzed using the t-test to see significant differences between the pretest and posttest results of the two groups. The results of the study show that there is a significant difference between the results of students' writing skills before and after the application of the storytelling method. The increase in the average value of the experimental class is higher than the control class. This shows that storytelling methods are effective in improving students' writing skills, especially in terms of idea development, story structure, and the use of creative language. Based on the research results, it can be concluded that storytelling learning is an effective learning and can be applied as an alternative method in improving students' writing skills at the junior high school level.